ASSESSMENT OF GENERAL ENGINEERING COURSES IN THE UAE UNIVERSITY AND RECOMMENDATION ACTIONS FOR IMPROVEMENT - Khoukhi, Maatouk (PUPIL: International Journal of Teaching, Education and Learning, 2021)
The current study examined the Architectural Engineering (AE) students at the College of Engineering (COE) at United Arab Emirates University (UAEU) learning outcomes through assessing three main engineering requirement courses. The assessment is based on the direct method which consists of the achievement of the students and their capability to demonstrate mastery through actual work or work products such as presenting the facts. The CLOs have been assessed through Course Work (Quizzes, Home works, and Term Projects) and Examinations (Midterm and Final Exams). The course learning outcomes (CLOs) for each course for the AE program have been analyzed in terms of the level of achievement and compared with the overall achievements of all students enrolled in the same courses at the COE. This assessment has been carried out for three continuous semesters fall 2019, spring 2020, and fall 2020. Indeed, some deficiencies in terms of CLOs achievement which has been set below 70% are recorded and remedial actions have been provided for improvement. The second part of this study consists of the comparison of the attainment level of the CLOs of GENG215 course between two consecutive semesters fall 2019 and spring 2020. Indeed, this period was characterized by the drastic change in the teaching method moving from the traditional way of face-to-face interaction with students to online teaching.